The Effects of Vole Bacillus Vaccination of African Mine Workers in the Northern Rhodesian Copper Mines. Issue 2 (April 1961) - Paul, R.
Abstract : African mine workers exposed to siliceous dust in the metalliferous mines of Northern Rhodesia were tuberculin tested; of 17, 697 tested, 13, 667 were tuberculin positive and 4, 030 negative. The negative reactors were divided at random into two approximately equal groups and 1, 984 were vaccinated with vole bacillus vaccine and 2, 046 were left unvaccinated. These two groups were subsequently followed up and their original radiological categories at the time of tuberculin testing and vaccination were compared with their radiological categories after varying periods of further dust exposure. The object of the investigation was to ascertain whether or not vaccination with vole bacillus vaccine introduced an acclerating factor in the rate of radiological change in pneumoconiosis. The results of the investigation showed that radiological changes in the two groups were minimal and that there was virtually no difference between them. No accelerated changes were recorded in the negative vaccinated group. This is regarded as evidence that anti-tuberculosis vaccine does not introduce an accelerating factor in pneumoconiosis. No case of pulmonary tuberculosis occurred in the negative vaccinated group. Three cases were recorded in the negative non-vaccinated group, suggesting that vaccination with vole bacillus vaccine affords some measure of protection against tuberculosis, and in view of the absence of any evidence that it had an accelerating effect in pneumoconiosis it appears desirable that miners should receive this protection.